Novel Ni@Co3O4 Web-like Nanofiber Arrays as Highly Effective Cathodes for Rechargeable Li-O2 Batteries. (1st December 2016) - Yu, Qiyao; Yu, Qilin; Sun, Wang; Wu, Haitao; Wang, Zhenhua; Rooney, David; Sun, Kening
Graphical abstract: Novel vertically self-standing Ni@Co3 O4 web-like nanofiber arrays were synthesized via a facile hydrothermal method. The Li-O2 batteries containing Ni@Co-WNFs cathode exhibit enormously enhanced performance in that a rare high specific capacity of 17118 mAh g −1 at a current of 0.1 mA cm −2 was demonstrated. Furthermore this was shown over 128 stable cycles with the capacity limited to 500 mAh g −1 . Highlights: Novel vertically self-standing Ni@Co3 O4 web-like nanofiber arrays were synthesized. They show high bifunctional activity for oxygen reduction and evolution reactions. A rare high specific capacity of 17118 mAh g −1 was demonstrated. 128 stable cycles was achieved with the capacity limited to 500 mAh g −1 . Abstract: Novel vertically self-standing Ni@Co3 O4 web-like nanofiber arrays (Ni@Co-WNFs) were synthesized via a facile hydrothermal method. The Co3 O4 nanofibers were grown on a macroporous nickel foam skeleton and intertwined together as a special web structure containing both micropores and mesopores. This self-standing and carbon free binder bifunctional electrocatalyst was directly used as a cathode for rechargeable Li-O2 batteries. These Li-O2 batteries containing Ni@Co-WNFs cathode exhibited enormously enhanced performance in that a rare high specific capacity of 17118 mAh g −1 at a current of 0.1 mA cm −2 was demonstrated. Furthermore, this was shown over 128 and 61 stable cycles with the capacity limited to 500 and 1000 mAh g −1 . The enhanced electrochemical performance is believed to be related to the extraordinary structure and outstanding catalytic activity of the Ni@Co-WNFs cathode, indicating that it is a promising electrode material for Li-O2 batteries.